# (x-2)cubed=0

## Simple and best practice solution for (x-2)cubed=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (x-2)cubed=0 equation:

Simplifying
(x + -2) * cubed = 0
Reorder the terms:
(-2 + x) * cubed = 0
Reorder the terms for easier multiplication:
bcdeu(-2 + x) = 0
(-2 * bcdeu + x * bcdeu) = 0
(-2bcdeu + bcdeux) = 0
Solving
-2bcdeu + bcdeux = 0
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'bcdeu'.
bcdeu(-2 + x) = 0
Subproblem 1Set the factor 'bcdeu' equal to zero and attempt to solve:
Simplifying
bcdeu = 0
Solving
bcdeu = 0
Move all terms containing b to the left, all other terms to the right.
Simplifying
bcdeu = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-2 + x)' equal to zero and attempt to solve:
Simplifying
-2 + x = 0
Solving
-2 + x = 0
Move all terms containing b to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + x = 0 + 2
Combine like terms: -2 + 2 = 0
0 + x = 0 + 2
x = 0 + 2
Combine like terms: 0 + 2 = 2
x = 2
Add '-1x' to each side of the equation.
x + -1x = 2 + -1x
Combine like terms: x + -1x = 0
0 = 2 + -1x
Simplifying
0 = 2 + -1x
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`